Porphyria Cutanea Tarda Associated With Acute Hemorrhagic Pancreatitis - Manasi Singh MD; Ashley Duckett MD; Marc Heincelman MD (SAGE Publishing, 2019)
Porphyria cutanea tarda (PCT) is a condition of dysregulated heme synthesis that leads to accumulation of photosensitizing precursors with resultant fragility and blistering of the skin. It can be hereditary or acquired and has been known to be associated with hepatic C virus, alcohol, HIV, and estrogen. In this article, we report an unusual presentation of PCT associated with acute hemorrhagic pancreatitis in a 57-year-old man. He presented initially to a community hospital with acute onset of epigastric abdominal pain and new-onset ascites. Lipase was elevated. Diagnostic paracentesis was grossly bloody. He was then transferred to our institution for concern for acute hemorrhagic pancreatitis. On arrival, physical examination demonstrated vesicles and bullae with erythematous bases, in different stages of healing seen over the dorsal aspects of both hands with scaling, scarring, and hypopigmentation and hyperpigmentation of the skin. Laboratory evaluation and skin biopsy confirmed the diagnosis of PCT. Search for an underlying etiology failed to reveal typical predisposing factors. This report illustrates that acute hemorrhagic pancreatitis may be an underlying etiology for PCT.